WAYS OF IMPROVEMENT POWER QUALITY IN THE CONTACT NETWORK WHEN THE AC LOCOMOTIVES - Vlasievskyi, S. V.; Skoryk, V. H. (Science and Transport Progress, 2007)
The article dials with one of the methods of voltage nonsinusoidality ratio distortion reduction in a.c. electric networks during electric locomotives operation.